CDKL5 modulates the plasticity of excitatory synapses via liquid–liquid phase separation - Mingjie Li; Ziai Zhu; Dan Li; Jinchao Wang; Mingjie Zhang; Qi-Wu Xu; Yu-Xian Zhang; Yongchuan Zhu; Jinwei Zhu; Zhi-Qi Xiong (Proceedings of the National Academy of Sciences, 2026)
Activity-dependent synaptic remodeling, essential for neural circuit plasticity, is orchestrated by central organizers within the postsynaptic density (PSD), including the scaffolding protein PSD95. However, the molecular mechanisms driving this process remain incompletely understood. Here, we identify cyclin-dependent kinase-like 5 (CDKL5), a protein associated with a severe neurodevelopmental condition known as CDKL5 deficiency disorder (CDD), as a critical regulator of structural plasticity at excitatory synapses. We show that CDKL5 undergoes liquid–liquid phase separation (LLPS) in vitro and in cultured neurons, forming cocondensates with PSD95. This LLPS-driven process spatially organizes synaptic components, specifically enabling the synaptic recruitment of Kalirin7 to promote dendritic spine enlargement. Pathogenic mutations disrupt condensate formation by impairing the LLPS capacity of CDKL5, directly linking phase separation defects to the pathogenesis of CDD. Our findings reveal a crucial role for CDKL5 in synaptic plasticity and establish LLPS as a fundamental mechanism by which CDKL5 coordinates molecular events to reorganize PSD architecture during synaptic remodeling.